CHARACTERISTICS OF APHORISMS RELATED TO THE CONCEPT OF "LOVE" - Gulnoza Turdiyeva Sayfullayevna (American Journals, 2023)
This article deals with the lexical-semantic analysis, national-cultural features of one of the scientific fields of linguistics, paremiology, inparticular, aphorisms related to the concept of "love".
Keywords: linguistic culture, paremia, proverb, adage, aphorism, semantic aspect, lexicalsemantic analysis, conceptual sign.